The Synergy of BWM and BUMDES as an Alternative for Improving the Welfare of SME - Fauzul Hanif Noor Athief; Linda Isma Cahyaningrum; Darlin Rizki; Afief El Ashfahany (Jurnal Masharif al-Syariah: Jurnal Ekonomi dan Perbankan Syariah, 2023)
This research paper investigates the symbiotic relationship between two institutions, BWM Imam Syuhodo and BUMDes Wonorejo, both committed to advancing the welfare of small and medium-sized enterprises (SMEs). The primary objective of this study is to provide a comprehensive exploration of the collaborative process between these entities and to offer a thorough analysis of the resultant impact on SMEs. Employing a qualitative research approach, this study incorporates field research methodology involving meticulous observations of the participating institutions, in-depth interviews with relevant stakeholders, and systematic documentation of physical and textual data. The findings of this research reveal a significant synergy between BWM Imam Syuhodo and BUMDes Wonorejo, facilitated under the auspices of the Financial Services Authority. This synergy was realized during the inauguration of BUMDes through a well-executed bazaar event, characterized by seamless operations and positive repercussions for local SMEs. The collaborative efforts have served as a vital conduit for entrepreneurs, offering expanded market access and exerting a transformative influence on the financial stability of SMEs. As a result, the surrounding community has witnessed tangible advancements in their business landscape, further underscoring the potential of such synergistic endeavors for SME welfare enhancement.